West-facing entrance of the Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The west-facing entrance of the Neelkanth Mahadev Temple is seen in the picture. The temple stands on a plinth. It is entered through a gate built into a later added boundary wall.